Cross-border loan portfolio diversification, capital requirements, and the European Banking Union - Esa Jokivuolle; Matti Virén (Bank of Finland, 2019)
We provide preliminary evidence of potential risk reduction benefits from banks' loan portfolio diversification cross-border within the Euro area. Using aggregate data on banking sector cor-porate loan losses for each Euro area member-state, our estimates suggest that the static diversification benefit could be substantial. The minimum capital needed to withstand the max-imum annual loss from a hypothetical fully diversified Euro area bank loan portfolio over the period 2001-2017 would have been only 40 % of the total capital needed to withstand the maximum losses on a country by country basis. We also calibrate the country-specific loan loss distributions and the Euro area portfolio's loss distribution to the Vasicek (2002) model, which underlies the Basel framework's Internal Ratings Based Approach. We find that the im-plied asset correlation parameter of a median country portfolio is about twice as large as that of the fully diversified Euro area portfolio.
URN:NBN:fi:bof-201905281211
Keywords: 330; pankit; luotot; euroalue